INTELLIGENT AGENTS BASED TRUSTED REVOCATION FOR SECURING CLUSTERING MANETS - Aranganathan, A.; Suriyakala, C. D. (APTIKOM Publisher, 2018)
Mobile Ad-hoc Network is a non-secure wireless network which has no infrastructure, dynamical topologyin which the nodes can move anywhere, may join or leave the network through multi-hop communication. In clusternetwork, all the nodes can select one Cluster Head for transmission of data to another Cluster Head through gatewayswhich is mainly used for saving energy of each node. Intelligent agents are used for collecting secure data fromneighboring nodes and inform to the trusted agent in clustered networks. Security plays major role in wireless medium.Detecting malicious node is also causing a major concern to damage the data packets. To avoid this problem of enteringmalicious node in networks and non-secured data, agents based trusted revocation in clustering mobile ad-hoc networkfor improving security with Certificate Authority to improve the network performance like high throughput, less latencytime and improved certificate revocation time using ns2 simulators.